Science Development Trends with the Metaphor of the Tree of Science State Islamic University of Maulana Malik Ibrahim Malang - Khoiriyah, Siti; Fuad, Ah Zakki; Bakar, M Yunus Abu (Lembaga Pendidikan Hikmatun Najah Blora, 2023)
This study aims to identify and analyze trends in science development using the metaphor of